Non-linearity of location factors - Christoph Hauser; Myriam Baumeler; Hannes Egli (European Regional Science Association (ERSA), 2012)
Location factors can be understood as a set of indicators of the locational advantage for firms of a certain region. Most studies on location factors presume a linearly increasing relationship between locational advantage and respective location factors. In this paper, this widespread assumption of linear relations is questioned. Analysis is made for two sets of regions: 813 Swiss municipalities larger than 2,000 inhabitants and for 151 districts in Switzerland. Significance levels of a linear regression model are compared to models where location factors are transformed in a non-linear way. These transformations can introduce a saturation effect, meaning that a location factor is beneficial to growth only up to a certain level, or a critical mass effect, meaning that a location factor is beneficial to growth only if it has already reached a certain level, or both a saturation effect and a critical mass effect at the same time. Nine different transformations are applied on five location factors for the municipality sample and for the district sample, resulting in ninety comparisons with the linear base models. For each of the five location factors, at least on case can be found where a transformation clearly improves t-statistics, suggesting a non-linearity. For instance, a critical mass effect can be observed for available business zones and for personal income taxes. The latter would suggest that some firms are more sensitive to personal income taxes as a location factor than others. The more sensitive ones will avoid regions with personal income taxes that are more expensive than average, making this location factor less relevant in avoided regions. Similarly, available building zones must reach a certain level in order to become relevant for locational advantage. For other location factors the opposite carries. A critical mass effect was found for corporate taxes and human capital, suggesting that an improvement of an already high level adds less than if starting from lower levels. Corporate tax and human capital thus seem to resemble a hygiene factor: corporate taxes hinder growth if they become too expensive, and missing human capital impedes growth while above-average human capital does not add as much anymore. Accessibility by public transport is associated with both a critical mass effect and a saturation effect. This means that accessibility should neither be a bottleneck nor luxurious. Results like these may have direct implications on location factor policy.
Keywords: H32; R11; R30; 330; firm location; location factors; non-linearity